PENGARUH BIMBINGAN KARIER TERHADAP KESIAPAN KERJA SISWA BIDANG KEAHLIAN TATA BUSANA DI SMK - Dian Wahyu Pertiwi (UNIVERSITAS SARJANAWIYATA TAMANSISWA, 2017)
The objectives of this study are to know (1) the influence of carrier guidance toward students’ working readiness, (2) carrier guidance, and (3) students’ working readiness. The type of this study was aex post facto. The sample was taken by using Slovin. Data collection technique used questionnaire to know carrier guidance and students’ working readiness. The validity test used Product Moment and reliability used Cronbach Alpha. Data analysis technique used descriptive analysis and hypothesis testing by using Product Moment that was started by normality and linearity test. This study shows that: (1) there was a positive and significant influence of carrier guidance toward students’ working readiness and carrier guidance gave a contribution toward students’ working readiness 51.3% while 48.7% was influenced by other factors, (2) carrier guidance was in fair category, and (3) students’ working readiness was in fair category. Key words: carrier guidance, working readiness